American ocelot [videorecording (DVD)] - Masters, Ben, 1988-; Masters, Ben, 1988-; Masters, Ben, 1988-; Masters, Ben, 1988- (PBS, 2023)
Chronicles the sad history, precarious present, and optimistic future for one of the United States' most endangered wild cats. Wildlife filmmaker Ben Masters documents these rare and elusive animals in South Texas while meeting with the biologists, the ranchers, and the cats themselves.